Analysis of the Teaching Difficulty by University Students of Arabic Language Education through Microteaching Practices/ Analisis Kesulitan Mengajar Mahasiswa Pendidikan Bahasa Arab Melalui Praktik Microteaching - Fadillah, Roojil (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2021)
Microteaching is one of the media that develops skills suitable for teachers in improving Arabic teaching skills. For prospective teachers, the advantages of implementing microteaching practice can provide an authentic experience and practice some skills so that future teachers can create an effective, efficient, and attractive Arabic learning process. This study aims to determine the level of teaching skills of prospective teachers with peers as supervisors, knowing the difficulties before and during the microteaching process. The approach in this research is robust, with quantitative descriptive as the method. After the data collected, quantitative data processing is carried out in the following ways: a) Editing, all documents are checked completeness after respondents fill in: b) Coding and Data entry, done manually: c) Data cleaning: d) Data is then analyzed, data analysis is done with simple univariate analysis. The results showed that students' skills in drawing up a Learning Implementation Plan (Rencana Pelaksanaan Pembelajaran) were 74.1%, student skills in providing learning media that supported learning were 76.4%, student skills in using learning methods were 77%, and student skills in conducting variations, discussions, explaining materials by 75%. The average score of prospective teachers in the microteaching of the Arabic Language Education Study Program of Muhammadiyah University of Yogyakarta is 76.4%. The difficulties faced by future teachers in microteaching practice with peers as tutors are summarized in several points, (1) Rpp Building Skills, (2) Incompatibility between reality in the classroom and RPP, (3) Lack of teacher confidence, (4) Difficulty using learning media, (5) Difficulty in teaching basic skills. The difficulties of basic teaching skills are opening and closing lessons, classroom management skills, group forming skills, explaining skills, and variation making skills.